Some fixed point theorems for pseudo ordered sets - Parameshwara Bhatta, S.; George, S. (Algebra and Discrete Mathematics, 2011)
In this paper, it is shown that for an isotone map f on a pseudo ordered set A, the set of all fixed points of f inherits the properties of A, namely, completeness, chain-completeness and weakly chain-completeness, as in the case of posets.